2017
DOI: 10.1037/ocp0000018
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employee assistance services on workplace outcomes: Results of a prospective, quasi-experimental study.

Abstract: Employee Assistance Programs (EAPs) are widely used to help employees experiencing personal or work-related difficulties that impact work productivity. However, rigorous research on the effectiveness of programs to improve work-related outcomes is lacking. The current study represents a major advance in EAP research by using a prospective, quasi-experimental design with a large and diverse employee base. Using propensity scores calculated from demographic, social, work-related, and psychological variables coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…It is well accepted that organisational P a g e |2 factors can influence the prevalence and severity of such problems, and promote improved outcomes. For example, evidence supports the positive influence on health and wellbeing of formal support systems such as professional counselling and resilience training (see for instance, Richmond, Pampel, Wood, & Nunes, 2017) and programs whereby peers are trained to provide counselling and support to one another (Revicki, Whitley, & Gallery, 1993;Scully, 2011). Relationships with colleagues and frontline managers (FLMs) can also be instrumental in reducing the severity of symptoms and encouraging positive post-traumatic growth (Oginska-Bulik, 2015;Prati & Pietrantoni, 2010;Somville, De Gucht, & Maes, 2016).…”
Section: Barriers To Frontline Manager Support For High-trauma Workermentioning
confidence: 99%
“…It is well accepted that organisational P a g e |2 factors can influence the prevalence and severity of such problems, and promote improved outcomes. For example, evidence supports the positive influence on health and wellbeing of formal support systems such as professional counselling and resilience training (see for instance, Richmond, Pampel, Wood, & Nunes, 2017) and programs whereby peers are trained to provide counselling and support to one another (Revicki, Whitley, & Gallery, 1993;Scully, 2011). Relationships with colleagues and frontline managers (FLMs) can also be instrumental in reducing the severity of symptoms and encouraging positive post-traumatic growth (Oginska-Bulik, 2015;Prati & Pietrantoni, 2010;Somville, De Gucht, & Maes, 2016).…”
Section: Barriers To Frontline Manager Support For High-trauma Workermentioning
confidence: 99%
“…Studies have documented the effectiveness of employee assistance programs to help employees with stress and mental health problems address those concerns and return to work as productive employees (Attridge et al., ; Jacobson, Jones, & Bowers, ; Nunes, Richmond, Pampel, & Wood, ; Richmond, Pampel, Wood, & Nunes, ; Sharar & Lennox, ). One example of such programs is critical incident stress debriefing, which has been found be effective (Attridge & VandePol, ; DeFraia, ).…”
Section: Part 2—elements Of Integral Modelmentioning
confidence: 99%
“…These questions were asked to get a better insight on those who answered that their institution did have an EAP. According to the study conducted by Richmond et al [6], the majority of businesses indicated that they used their EAP in correlation with a disaster and incorporated the EAP as such. The data from this study contradicts Richmond et al slightly, where all respondents said that their EAP was located in a Human Resource document.…”
Section: Employee Assistance Programsmentioning
confidence: 99%
“…The occurrence of natural disasters in the workplace creates stress within employees, and EAPs are becoming an avenue to help them cope with the stressors of disaster [5]. While the amount of EAP efficacy research is thin, current studies show that EAPs can be beneficial and effective to the employees who choose to use them [6].…”
Section: Introductionmentioning
confidence: 99%